2020
DOI: 10.1097/acm.0000000000003696
|View full text |Cite
|
Sign up to set email alerts
|

Struggles and Tensions in Antiracism Education in Medical School: Lessons Learned

Abstract: Purpose Faculty from different racial and ethnic backgrounds developed and piloted an antiracism curriculum initially designed to help medical students work more effectively with patients of color. Learning objectives included developing stronger therapeutic relationships, addressing the effects of structural racism in the lives of patients, and mitigating racism in the medical encounter. Method The antiracism curriculum was delivered and evaluated in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 16 publications
0
32
0
2
Order By: Relevance
“…Biological conceptualizations of race, which are deeply embedded in medical education [ 99 ], contribute to institutional racism impacting on student learning, and ultimately racial health inequalities [ 99 , 170 ]. “Anti-racist” curricula shift teaching about race as a biological variable to that of a social construct, thus prompting explanations about health inequalities that focus on equity and discrimination rather than spurious genetic explanations [ 99 , 164 , 171 173 ]. There is the potential for anti-racist curricula to re-frame conceptions and misconceptions of race and racism, that impact on values, cultures and norms [ 163 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biological conceptualizations of race, which are deeply embedded in medical education [ 99 ], contribute to institutional racism impacting on student learning, and ultimately racial health inequalities [ 99 , 170 ]. “Anti-racist” curricula shift teaching about race as a biological variable to that of a social construct, thus prompting explanations about health inequalities that focus on equity and discrimination rather than spurious genetic explanations [ 99 , 164 , 171 173 ]. There is the potential for anti-racist curricula to re-frame conceptions and misconceptions of race and racism, that impact on values, cultures and norms [ 163 ].…”
Section: Resultsmentioning
confidence: 99%
“…22 In today's learning environment, antiracism education is expected to create an inclusive learning environment that engages communities while acknowledging discomfort, tension, and vulnerability when addressing issues centered on race. 8,23,24 When combined with a critical andragogy approach and culturally relevant and inclusive methodologies, antiracism education can serve as a tool to transform and equip faculty with the knowledge, skills, confidence, and empowerment to own their teaching, agency, and activism. 25 To successfully deliver antiracism education, faculty need professional development that is informed by the history and structure of racism so they can address the implicit and explicit biases that propagate racist ideology.…”
Section: Components Of Antiracism Educationmentioning
confidence: 99%
“…[6][7][8] Schools that have implemented social justice curricula have highlighted the importance of teaching students about these topics and shown that dedicated curricula can yield strategies to advance the conversation surrounding racism in healthcare. [9][10][11] In addition, many medical schools have released commitments to combat institutional racism in other ways beyond the curriculum, including community partnerships and creating inclusive environments for a diverse workforce. 12 Scientific journals have expressed similar commitments.…”
Section: Educational Goalsmentioning
confidence: 99%